2002
DOI: 10.1046/j.1525-1314.2002.00206_20_7.x
|View full text |Cite
|
Sign up to set email alerts
|

Melt loss and the preservation of granulite facies mineral assemblages

Abstract: The loss of a metamorphic fluid via the partitioning of H 2 O into silicate melt at higher metamorphic grade implies that, in the absence of open system behaviour of melt, the amount of H 2 O contained within rocks remains constant at temperatures above the solidus. Thus, granulite facies rocks, composed of predominantly anhydrous minerals and a hydrous silicate melt should undergo considerable retrogression to hydrous upper amphibolite facies assemblages on cooling as the melt crystallizes and releases its H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
211
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(217 citation statements)
references
References 44 publications
(65 reference statements)
6
211
0
Order By: Relevance
“…In contrast, metapelites within the domes have been partly reequilibrated through back-reaction with the melt during cooling (e.g. White and Powell 2002). Consequently, the temperature of 790-850°C estimated from the ultramafic and calc-silicate parageneses should therefore be the closest estimate of the temperature peak ( Fig.…”
Section: M2 Eventmentioning
confidence: 99%
“…In contrast, metapelites within the domes have been partly reequilibrated through back-reaction with the melt during cooling (e.g. White and Powell 2002). Consequently, the temperature of 790-850°C estimated from the ultramafic and calc-silicate parageneses should therefore be the closest estimate of the temperature peak ( Fig.…”
Section: M2 Eventmentioning
confidence: 99%
“…In the KFMASH system, sapphirine þ silicate melt can coexist above approximately 900 C (Kelsey et al, 2005) implying that the sapphirine assemblages along with the co-spatial magnesian metapelitic granulites are melt-bearing UHT assemblages. Using isochemical sections in the NCKFMASH model system, White et al (2001) and White and Powell (2002) have demonstrated that in a closed system (i.e., one from which no melt was lost), granulite facies mineral assemblages coexist with melt. To avoid complete retrogression, some melt loss or separation from residual mineral assemblages must occur (e.g., Powell and Downes, 1990;Kriegsman, 2001;Brown, 2002;White and Powell, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Using isochemical sections in the NCKFMASH model system, White et al (2001) and White and Powell (2002) have demonstrated that in a closed system (i.e., one from which no melt was lost), granulite facies mineral assemblages coexist with melt. To avoid complete retrogression, some melt loss or separation from residual mineral assemblages must occur (e.g., Powell and Downes, 1990;Kriegsman, 2001;Brown, 2002;White and Powell, 2002). In the case of melt segregation rather than loss, the retrogression depends on the size of the equilibration volume (St€ uwe, 1997), which decreases with falling temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations